Pengenalan Nilai-nilai Kearifan Lokal Melalui Kegiatan Rebo Nyunda Pada Anak Usia 5-6 Tahun di RA Sabilul Muttaqin Cikampek Timur - Assiyah, Shela; Syafrida, Rina; Riana, Nancy (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to explore the introduction of local wisdom values ​​in children aged 5-6 years through Rebo Nyunda activities at RA Sabilul Muttaqin, East Cikampek. Rebo Nyunda activities have been carried out for 3 consecutive years and continue to this day, routinely held once a week on Wednesdays. The aim of this activity is to introduce local wisdom values ​​to young children from a very young age. During the activity, children were introduced to various aspects of Sundanese culture and language through the introduction of Sundanese pupuh, regional songs, and Sundanese vocabulary. The introduction of regional languages ​​aims to improve regional language skills and enrich children's vocabulary. Apart from that, children were also introduced to traditional Sundanese games such as Snake Dragon, Rubber Jump, Hompimpa, Engkle, and Congklak, as well as the traditional tools used in these games. It is hoped that the introduction of local wisdom values ​​through Rebo Nyunda activities can shape the character of children who have high cultural awareness, respect their ancestral heritage, and have a sense of love for their homeland. The research results show that Rebo Nyunda activities have succeeded in creating an environment that supports the introduction and development of local wisdom values ​​in early childhood at RA Sabilul Muttaqin, East Cikampek.